sn-metrizable spaces and related matters - Zhiming Luo (International Journal of Mathematics and Mathematical Sciences)
We give a mapping theorem on sn-metrizable spaces, discuss relationships among spaces with point-countable sn-networks, spaces with uniform sn-networks, spaces with locally countable sn-networks, spaces with σ-locally countable sn-networks, and sn-metrizable spaces, and obtain some related results.